Analisis Luaran Maternal Dan Neonatal Berdasarkan Indeks Massa Tubuh (IMT) Pada Pra Hamil Di Bangkalan - Qomari, Selvia Nurul; Nikmah, Nurun; Antina, Rila Rindi (Universitas Muhammadiyah Gresik, 2024)
Pregnancy is a crucial period in a woman's life. Although it is a physiological process, pregnancy carries certain warning signs and complications that can threaten the health of both mother and baby. Nutritional issues experienced by a woman before and during the early stages of pregnancy can significantly impact the quality of the pregnancy and the subsequent stages of life. This study aims to analyze maternal and perinatal outcomes based on pre-pregnancy BMI. This research employs an analytic design with a retrospective approach. The study’s variables include the independent variable of pre-pregnancy BMI, while the dependent variables are maternal outcomes (gestational age at delivery) and perinatal outcomes, including low birth weight and asphyxia. The population for this study consisted of women who gave birth in Bangkalan Regency. The sampling technique used was probability sampling, specifically purposive sampling. The statistical test using Spearman Rank showed a p-value of 0.802 (>0.05), indicating no correlation between pre-pregnancy BMI and gestational age at delivery. A p-value of 0.277 (>0.05) indicated no significant relationship between pre-pregnancy BMI and birth weight. However, a p-value of 0.005 (<0.05) and a correlation coefficient of 0.287 indicated a weak correlation between pre-pregnancy BMI and asphyxia/Apgar score. It is essential for pregnant women to monitor their weight gain during pregnancy to align with recommended guidelines.